Modeling and Simulation of Thin Layered Composites Under Non-mechanical Stimuli - Song, Ruyue; Tajeddini, Vahid; Muliana, Anastasia (Frontiers in Materials, 2020)
This study presents a nonlinear deformation analysis of a thin composite plate undergoing shape reconfigurations triggered by electric field inputs. The composite plate consists of electro-active and inactive (substrate) layers. Prescribing electric field inputs to the electro-active layer induces large curvatures in the composites, while the in-plane stretch is relatively small. This has a consequence that only shapes with zero (or nearly zero) Gaussian curvature can be attained by prescribing the electric field, which leads to snap-through shape reconfigurations in order to achieve developable surfaces. When the substrate is made of an elastic layer, the shape returns to its original planar configuration upon removal of the electric field. In order to fully or partially retain the reconfigured shape upon removing the electric field input, a substrate layer made of a shape memory polymer is considered. Shape reconfigurations and retentions of the composites having elastic substrate and shape memory substrate are simulated.